Keistimewaan I’jaz Al-Qur’an: Bukti Kebenaran yang Abadi - Fitri, Dini; Rikzhan, M; Dwi Perwira, Zahra; Sawitri, Riska (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The Qur’an is the holy book of Islam, believed to be the revelation of Allah (SWT) and possesses extraordinary uniqueness, one of which is the concept of I’jaz al-Qur’an(the inimitability of the Qur’an). This concept signifies that the Qur’an cannot be matched or imitated by anyone, whether in terms of its language, content, or message. This study aims to examine the distinctive aspects of the Qur’an’s inimitability as an eternal proof of its truth and relevance across all times. This research employs a qualitative approach through library research, analyzing Qur’anic verses as well as the perspectives of scholars and exegetes. The findings indicate that the inimitability of the Qur’an encompasses several dimensions, including linguistic excellence (balaghah), scientific insights, the perfection of its legal system, and its compatibility with the development of modern knowledge. These unique features not only serve as evidence of the Qur’an as a divine revelation but also present an open challenge to humanity to produce something comparable, a challenge that remains unmet to this day. In conclusion, the inimitability of the Qur’an stands as an authentic and everlasting proof of its truth, continuously relevant to human life. Understanding this concept is expected to strengthen the faith and conviction of Muslims in the Qur’an as a comprehensive guide for life.